2001
DOI: 10.1128/mcb.21.23.7901-7912.2001
|View full text |Cite
|
Sign up to set email alerts
|

Yeast AMP Pathway Genes Respond to Adenine through Regulated Synthesis of a Metabolic Intermediate

Abstract: In Saccharomyces cerevisiae, AMP biosynthesis genes (ADE genes) are transcriptionally activated in the absence of extracellular purines by the Bas1p and Bas2p (Pho2p) transcription factors. We now show that expression of the ADE genes is low in mutant strains affected in the first seven steps of the pathway, while it is constitutively derepressed in mutant strains affected in later steps. Combined with epistasy studies, these results show that 5-phosphoribosyl-4-succinocarboxamide-5-aminoimidazole (SAICAR), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(148 citation statements)
references
References 44 publications
9
138
0
1
Order By: Relevance
“…A genetic analysis of mutants unresponsive to adenine has shown that adenine needs to be taken up and metabolized to ADP to exert its regulatory role (Guetsova et al 1997;Rébora et al 2001). This is consistent with the observation that extracellular hypoxanthine downregulates expression of an ADE1-lacZ fusion while guanine has little effect (Guetsova et al 1997) because hypoxanthine can be converted to adenylic nucleotides while guanine cannot ( Figure 15).…”
Section: Regulation Of Pyrimidine Metabolismsupporting
confidence: 62%
See 1 more Smart Citation
“…A genetic analysis of mutants unresponsive to adenine has shown that adenine needs to be taken up and metabolized to ADP to exert its regulatory role (Guetsova et al 1997;Rébora et al 2001). This is consistent with the observation that extracellular hypoxanthine downregulates expression of an ADE1-lacZ fusion while guanine has little effect (Guetsova et al 1997) because hypoxanthine can be converted to adenylic nucleotides while guanine cannot ( Figure 15).…”
Section: Regulation Of Pyrimidine Metabolismsupporting
confidence: 62%
“…Strikingly, most of the deregulated mutants affected the ADE13 gene encoding adenylosuccinate lyase, suggesting a key role for this step of the pathway ( Figure 15) (Rébora et al 2001). Further genetic analyses revealed that AICAR (59-phosphoribosyl-5-amino-4-imidazole carboxamide) and SAICAR (succinyl-AICAR), the metabolic intermediates just downstream and upstream of Ade13, respectively, play a pivotal role by promoting interactions between Bas1 and Pho2 (Rébora et al 2001(Rébora et al , 2005. Several lines of evidence supported this idea.…”
Section: Regulation Of Pyrimidine Metabolismmentioning
confidence: 99%
“…For the third IMA pathway, adenine biosynthesis, it is clear that one (or both) of the two metabolites AICAR and SAICAR induces transcriptional activation via the transcription factor Bas1; however, it is not fully understood which is the major regulator (2). We find that the enzyme Ade17 has a higher induction than any other enzyme in the pathway (Fig.…”
Section: Gene Expression Profiles In Amino Acid and Nucleotide Biosynmentioning
confidence: 76%
“…To achieve this regulation, a variety of strategies can be used, involving different interplay between metabolites, enzymes, and regulatory proteins. In many cases involving model organisms, the regulatory framework that controls this process is known, and research over past decades has revealed a number of different regulatory strategies (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…Indeed, apart from playing a crucial role in the control of phosphate homeostasis, Pho2 together with the transcription factor Bas1 co-regulates the expression of the so-called ADE regulon that includes genes involved in the de novo synthesis of purines (Daignan-Fornier and Fink 1992). Consistently, a recent transcriptome analysis revealed that the metabolic intermediate AICAR (5 0 -phosphoribosyl-5-amino-4-imidazole carboxamide), which was previously identified as a transcriptional regulator of the purine pathway genes (Rebora et al 2001;Rebora et al 2005), also mediates the expression of several PHO genes ). These authors reported that Pho4 and Bas1 compete for Pho2 binding and that AICAR stimulates the interaction between either Pho4 or Bas1 with Pho2.…”
Section: The Protein Kinase Sch9mentioning
confidence: 78%